(untitled) (Revista de Ciências Agroveterinárias, 2017)
The yield of lumber is one of the main parameters of evaluation of log sawing. Using this information, you can judge the quality of the conversion of logs into sawed parts. This variable indicates the percentage of the original volume of the log that has been transformed into lumber. Therefore, this study aimed to expand knowledge of the mechanical processing of Eucalyptus wood. For this, we employed 72 logs of three species: Eucalyptus dunnii, Eucalyptus grandis and Eucalyptus saligna. We compared the income of lumber of the three species, as well as three diameter classes per species. Additionally we evaluated some characteristics of the shape of the stem and phenomena that occurred during the sawing. The results showed that the larger diameter logs from E. saligna and E.grandis obtained the best performances in income, then the logs of the two intermediate species. The logs from E. dunnii had the worst performance among the three diameter classes, due to the shape of the logs and the manifestation of growth stresses during sawing.